Junin Virus Triggers Macrophage Activation and Modulates Polarization According to Viral Strain Pathogenicity - Ferrer, María F.; Thomas, Pablo; López Ortiz, Aída O.; Errasti, Andrea E.; Charo, Nancy; Romanowski, Victor; Gorgojo, Juan; Rodriguez, María E.; Carrera Silva, Eugenio A.; Gómez, Ricardo M. (Frontiers in Immunology, 2019)
The New World arenavirus Junin (JUNV) is the etiological agent of Argentine hemorrhagic fever (AHF). Previous studies of human macrophage infection by the Old-World arenaviruses Mopeia and Lassa showed that while the non-pathogenic Mopeia virus replicates and activates human macrophages, the pathogenic Lassa virus replicates but fails to activate human macrophages. Less is known in regard to the impact of New World arenavirus infection on the human macrophage immune response. Macrophage activation is critical for controlling infections but could also be usurped favoring immune evasion. Therefore, it is crucial to understand how the JUNV infection modulates macrophage plasticity to clarify its role in AHF pathogenesis. With this aim in mind, we compared infection with the attenuated Candid 1 (C#1) or the pathogenic P strains of the JUNV virus in human macrophage cultures. The results showed that both JUNV strains similarly replicated and induced morphological changes as early as 1 day post-infection. However, both strains differentially induced the expression of CD71, the receptor for cell entry, the activation and maturation molecules CD80, CD86 and HLA-DR and selectively modulated cytokine production. Higher levels of TNF-α, IL-10 and IL-12 were detected with C#1 strain, while the P strain induced only higher levels of IL-6. We also found that C#1 strain infection skewed macrophage polarization to M1, whereas the P strain shifted the response to an M2 phenotype. Interestingly, the MERTK receptor, that negatively regulates the immune response, was down-regulated by C#1 strain and up-regulated by P strain infection. Similarly, the target genes of MERTK activation, the cytokine suppressors SOCS1 and SOCS3, were also increased after P strain infection, in addition to IRF-1, that regulates type I IFN levels, which were higher with C#1 compared with P strain infection. Together, this differential activation/polarization pattern of macrophages elicited by P strain suggests a more evasive immune response and may have important implications in the pathogenesis of AHF and underpinning the development of new potential therapeutic strategies.